Synthesis of Ethylene Glycol Diesters as Bio-Lubricant from Jatropha Methyl Esters - E.Mokhtar, Salma M.; Abdella, Babiker K.; Mahjub, ImadEldeen .A; Abd Elmawla4, Maha .A. (Gezira Journal of Engineering and Applied Sciences, 2019)
The synthesis of ethylene glycol diesters as bio-lubricant was achieved via Trans- esterification reaction of Jatropha Methyl Ester (JME).The experimental strategy consists from two Transesterification reaction steps.At first step, Jatropha oil was extracted and characterized and then converted into JME. Then JME was converted to biolubricant at 120 o C, molar ratio of ethylene glycol to JME was 1:3.5 through 2.5 hr. and sodium meth-oxide was used as a catalyst was 0.8% w/w of total reactants. The physicochemical properties of the bio-lubricant were investigated. Kinematic viscosity at 40 o C was 16 cSt, kinematic viscosity at 100 o C was 4.54 cSt, viscosity index was 195.83 and the pour point was 18 o C.FTIR spectrum for JME to confirm the ester group was 1741cm -1 while for bio-lubricant was 1743cm -1 .It was found that the synthesis bio-lubricant data agree with petroleum base lubricant that reported by previouswork investigation. ملخص الدراسة       تم اصطناع استرات الايثلين جلايكول الثنائية كزيت تزييت حيوي عن طريق  تفاعل الاسترة التحويلية لاسترات ميثيل الجاتروفا. استراتيجية التجربة اشتملت على خطوتين من تفاعل الاسترة التحويلية. الخطوة  الاولي تم استخلاص زيت الجاتروفا حيث تم دراسة خصائصه ثم حول الى استرات ميثيل الجاتروفا. حولتاسترات ميثيل الجاتروفا الى الزيت الحيوي عند درجة حرارة 120م◦ وذلك بنسبة مولية للايثلينجلايكول الى استرات ميثيل الجاتروفا (3.5:1)وكان زمن التفاعل 2.5 ساعة باستخدام ميثو اكسيد الصوديوم كعامل حفاز بنسبة 0.8% من الوزن الكلي للمتفاعلات. درست الخصائص الفيزيوكيميائية للزيت الحيوي مثل اللزوجة الكاينماتيكية عند 40 م◦ هي 16 سنتي ستوك ، واللزوجة الكينماتيكية عند100 م◦ هي 4.54 سنتي ستوك ، ومعامل اللزوجة هو 195.83 ، ونقطة الانسكاب هي 18 م◦. وايضا تم إجراء التحليل الطيفي بواسطة الاشعة تحت الحمراء لاستراتجاتروفا الميثيل  للتأكد من مجموعة الاستر كان عند طول موجي 1741 سم -1 بينما الطول الموجي للزيت الحيوي 1743 سم -1 . وجد ان نتائج الزيت الحيوي الذي تم اصطناعه  تتفق مع نتائج زيت الاساس البترولي في الدراسات السابقة.